Critical Thinking-Related Challenges to Academic Writing: A Case of Indonesian Postgraduate Students at a UK University - Samanhudi, Udi; Linse, Caroline (Lingua Cultura, 2019)
This research reported Indonesian studentsâ€™ perspectives on challenges in writing a critical academic essay and factorsÂ causing those challenges in a university in the UK. It was a qualitative method in nature and used a semi-structuredÂ interviewing technique with open-ended questions as the main method for data collection. The results indicate four mainÂ problems the participantsâ€™ encountered in relation to critical thinking realization in their essay writing which include clarityÂ of ideas presented, lack of critical analysis, lack of critical evaluation, and lack of precision. This research also finds threeÂ important factors causing those problems of critical thinking realization by the students in their essay writings namelyÂ lack critical awareness, lack of understanding of the critical thinking concept, and differences of academic requirementsÂ between Indonesian and British context. This research is expectedly useful as an input in the re-design of syllabi and in theÂ improvement of writing instruction that aims to promote especially international Indonesian studentsâ€™ critical thinking inÂ university-level education, in line with properly addressing studentsâ€™ needs and developing CT pedagogy in the site.